2005
DOI: 10.1088/0022-3727/38/4/r01
|View full text |Cite
|
Sign up to set email alerts
|

Plasmas in high speed aerodynamics

Abstract: A review is presented of the studies in the former Soviet Union and in the USA of the mutual interactions of plasmas and high speed flows and shocks. There are reports from as early as the 1980s of large changes in the standoff distance ahead of a blunt body in ballistic tunnels, significantly reduced drag and modifications of travelling shocks in bounded weakly ionized gases. Energy addition to the flow results in an increase in the local sound speed that leads to expected modifications of the flow and change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
89
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(98 citation statements)
references
References 85 publications
(114 reference statements)
0
89
0
4
Order By: Relevance
“…[11][12][13][14] Specifically, in high-speed flows, several experimental studies have demonstrated the influence of the plasma on shock wave. [15][16][17][18] Many of these investigations have been performed with shock waves, generated by an electrically pulsed discharge, propagating along the low-pressure-unconstricted dc glow discharge.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Specifically, in high-speed flows, several experimental studies have demonstrated the influence of the plasma on shock wave. [15][16][17][18] Many of these investigations have been performed with shock waves, generated by an electrically pulsed discharge, propagating along the low-pressure-unconstricted dc glow discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with mechanical one, the method of high-speed §ow control based on plasma deposition possesses, at least, two advantages: inertialess and §exibility (electronic control of magnitude and location of plasma impact). Numerous potential applications can be considered (still extemporized in the most cases) for this technique [3,7].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the problem of flow active control by low-temperature plasma is considered to be one of the most booming realms of aerodynamics [Bletzinger et al, 2005, Moreau, 2007. One of the main practical advantages of plasma-assisted flow control is its zero reaction time.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the plasma mechanisms of external flow modification, shock wave reconfiguration and drag force reduction were considered as an important alternative to traditional solutions for thermal management [Bletzinger et al, 2005]. The paper [Klimov et al, 1982] was one of the first articles devoted to the impact of plasma effects on shock wave propagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation